The impact of strategic management towards corporate performance - a case of Malaysian - Ng , Kah Lok (2023)
The very main objective of this research is to study the relationship between independent variables which are “Strategic Planning”, “Strategic Formulation”, “Strategic Implementation”, “Strategic Evaluation” and dependent variables which is “Corporate Performance”.